KARAKTERISASI DAN SKRINING FITOKIMIA EKSTRAK DAUN JAMBLANG (Syzygium Cumini L. (Skeels)) - 0, mona asiah; sari, Febia (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
Jamblang (Syzygium cumini L. (Skeels)), is a plant that is thought to contain tannin compounds. Of the various types of polyphenols, tannin is an active ingredient that is used as a natural coagulant. Tannin, or known as tannic acid, is a water-soluble polyphenol that contains many functional groups such as hydroxyl or carboxyl (Bele et al., 2010). Characterization of simple drugs is important to do to determine the authenticity and quality of simple drugs which will later become standards if the simple drugs are used as test materials. The purpose of this study was to determine the characteristics of jamblang leaf simple drugs. The study began with sampling, determination, making simple drugs, characterization including macroscopic tests, microscopic tests, determination of water content, ash content, acid-insoluble ash content and phytochemical screening. Data were analyzed using descriptive methods. Macroscopic and microscopic characterization of jamblang leaves showed that jamblang leaves are single, thick leaves. The leaf blades are oval, the edges are flat, the leaf veins are pinnate, and the upper surface is shiny. Microscopic examination of jamblang leaves shows that jamblang leaves have a cuticle layer and have anomotetracyclic stomata. The water content of the ethanol extract of jamblang leaves is 5.98%, the total ash content is 4.15%, and the acid-insoluble ash content is 0.81%. The results of phytochemical screening of jamblang leaf extract contain steroids/triterpenoids, glycosides, saponins, flavonoids, tannins, and alkaloids.